2017
DOI: 10.1007/s10797-017-9454-3
|View full text |Cite
|
Sign up to set email alerts
|

Capital taxation, investment, growth, and welfare

Abstract: This paper formulates a model of economic growth to study the effects of broad capital taxation (of profits, dividends, and capital gains) on macroeconomic outcomes in small open economies. A framework of exogenous growth permits modeling countries in transition to a country-specific steady state and to discern steady-state and transitory effects of shocks on economic outcomes. The chosen framework is amenable to structural estimation and, in view of the parsimony of the model, fits data on 79 countries over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The effects of tax policies on investment and growth is an ongoing important debate within economic research. While many papers find that lower taxes have positive impacts on macroeconomic variables (Lee and Gordon 2005;Bösenberg, Egger, and Zoller-Rydzek 2017), the debate persists as others find no long term effects (eg. Stokey and Rebelo (1995)) and there is substantial variation across studies in size of the effect.…”
Section: The Effectiveness Of Tax Incentives: What We Knowmentioning
confidence: 99%
“…The effects of tax policies on investment and growth is an ongoing important debate within economic research. While many papers find that lower taxes have positive impacts on macroeconomic variables (Lee and Gordon 2005;Bösenberg, Egger, and Zoller-Rydzek 2017), the debate persists as others find no long term effects (eg. Stokey and Rebelo (1995)) and there is substantial variation across studies in size of the effect.…”
Section: The Effectiveness Of Tax Incentives: What We Knowmentioning
confidence: 99%
“…Hence, the threshold is latent and needs to be estimated. Moreover, the figure points to two further threshold levels in ownfunds space as we raise funds further beyond the level of the marginally less constrained entrepreneur: the first one occurs for the marginal managerial firm at   , 9 and the second one for the marginal dividend-paying managerial firm at   . The latter two regimes are inherently observable -it is known which firms have dispersed ownership and which do not; and it is known which of the firms with dispersed ownership pay dividends and which do not.…”
Section: Econometric Strategymentioning
confidence: 95%
“…The simulation model shows that the model has better prediction ability and accuracy [10]. Bsenberg S(2018) In order to study the impact of capital tax on macroeconomic output, it makes an empirical analysis based on the data samples of 79 countries from 1996 to 2011 and exogenous growth model, it is found that reducing capital tax has a positive impact on output [11]. Mushtaq(2016) Based on the time series data of Pakistan from 1961 to 2013, it is found that there is no Granger causality between the banking savings & lending business and the economic growth in the long term and short term through cointegration test and Granger causality test, but the economic growth affects the bank's lending business, so the lending procedures should be simplified during the peak period of economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%